2013
DOI: 10.1128/jvi.02374-13
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Mapping and Analysis of Kaposi's Sarcoma-Associated Herpesvirus 3′ UTRs Identify Differential Posttranscriptional Control of Gene Expression in Lytic versus Latent Infection

Abstract: b 3= untranslated regions (UTRs) are known to play an important role in posttranscriptional regulation of gene expression. Here we map the 3= UTRs of Kaposi's sarcoma-associated herpesvirus (KSHV) using next-generation RNA sequencing, 3= rapid amplification of cDNA ends (RACE), and tiled microarray analyses. Chimeric reporters containing the KSHV 3= UTRs show a general trend toward reduced gene expression under conditions of latent infection. Those 3= UTRs with a higher GC content are more likely to be associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 84 publications
2
29
0
Order By: Relevance
“…These results were obtained from RNA-seq analysis of ALT-enriched RNA, but similar percentages were observed at the same position in libraries from non-ASO-enriched RNA (all raw reads are available in the NCBI Sequence Read Archive under accession code SRP082699). As the two genome-encoded adenine residues upstream of position 130873 interfere with determining the exact start of this poly(A) tract, this result is consistent with the published TTS at positions corresponding to 130870 to 130872 in the JSC1 genome (13,19,21,59,60).…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…These results were obtained from RNA-seq analysis of ALT-enriched RNA, but similar percentages were observed at the same position in libraries from non-ASO-enriched RNA (all raw reads are available in the NCBI Sequence Read Archive under accession code SRP082699). As the two genome-encoded adenine residues upstream of position 130873 interfere with determining the exact start of this poly(A) tract, this result is consistent with the published TTS at positions corresponding to 130870 to 130872 in the JSC1 genome (13,19,21,59,60).…”
Section: Resultssupporting
confidence: 79%
“…From these studies at least 16 potential lncRNAs have been reported (13,(19)(20)(21), although there are discrepancies between the different approaches (Table 1). Seven potential lncRNAs found by tiling microarray (19,20) were not detected by subsequent RNA-seq studies (13,21,59,60). We sought to integrate these and prior studies (1, 13, 19-21, 50, 59-61) into an updated, comprehensive map of KSHV transcription annotations (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In latently infected B cells, the K3 promoter is free of RNA polymerase (RNAP) II, while the K5 promoter is occupied by stalled RNAP II, showing that the K5 gene is poised for expression and is expressed independently of RTA during latency (87,88). Recent studies have begun to characterize the 3= untranslated regions (UTRs) of KSHV protein-encoding genes (89,90): while the K5 3= UTR carries a modest stabilizing effect, the K3 3= UTR exhibits a destabilizing activity (89), miR-K3 has a small inhibitory effect on the a K3 3= UTR reporter activity (90), and the 3= UTR of K3 is among the shortest of all the 3= UTRs in the KSHV genome (89,90). Finally, while vIRF1 has been shown to bind to a region adjacent to the K3 coding sequence (91), its binding region is 1 kb downstream of the transcription start site (TSS) of K3 (40,56), raising questions about the mechanism by which vIRF1 might regulate K3 gene expression.…”
Section: Discussionmentioning
confidence: 99%